Selecting Resolving Agents with Respect to Their Eutectic Compositions. Issue 3 (21st January 2016) - Szeleczky, Zsolt; Semsey, Sándor; Bagi, Péter; Pálovics, Emese; Faigl, Ferenc; Fogassy, Elemér
Abstract: In order to develop a resolution procedure for a given racemic compound, the first and the most important step is finding the most suitable resolving agent. We studied 18 individual resolutions that were carried out with resolving agents having high eutectic composition. We found that very high enantiomeric excess values were obtained in all cases. We assume that the eutectic composition of a given resolving agent is one of the most important properties that should always be considered during the search for the most efficient resolving agent. Chirality 28:230–234, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :